Predicted Chemotherapy Benefit for Breast Cancer Patients With Germline Pathogenic Variants in Cancer Susceptibility Genes. Issue 1 (18th September 2020) - Kurian, Allison W; Ward, Kevin C; Abrahamse, Paul; Hamilton, Ann S; Katz, Steven J
Abstract: Breast cancer patients increasingly undergo genetic testing. To examine chemotherapy indications for germline pathogenic variant (PV) carriers, we linked results of germline testing to Georgia and California Surveillance, Epidemiology, and End Results registry records, including 21-gene recurrence score (RS) results, for breast cancer patients diagnosed in 2013-2017. All statistical tests were 2-sided. Patients (N=37 349) had RS results of whom 714 had BRCA1, BRCA2, CHEK2, ATM, PALB2, or Lynch syndrome ( MLH1, MSH2, MSH6, PMS2 ) PVs. For women aged 50 years or older at breast cancer diagnosis, RS often exceeded the chemotherapy benefit threshold (≥26) with BRCA1 (71.7% vs 14.4% with none; P <.001), PALB2 (37.1%; P = .001), and BRCA2 (44.3%; P < .001) PVs. Results were similar for women diagnosed at younger than 50 years of age. PVs in BRCA1, but not BRCA2, PALB2, ATM, CHEK2, or Lynch syndrome genes, were associated with elevated RS on multivariable analysis ( P < .001). Results may inform RS testing decisions in breast cancer patients with PVs.